স্বায়ত্তশাসন স্বাধিকার ও স্বাধীনতা - চৌধুরী, আবদূর রউফ (ঢাকা : কথাপ্রকাশ, 2010)
Political history of Bangladesh, since 1947-1971.
In Bengali; includes passages in English.
Keywords: Bangladesh -- Politics and government